PERILAKU WAJIB PAJAK UMKM DALAM MENJALANKAN KEWAJIBAN PERPAJAKANNYA - Tri Yuniati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study is to analyze how the behavior of MSME taxpayers in carryingout their tax obligations. The research population is MSME taxpayers domiciled inSurabaya, the sample of this study involved 52 respondents using purposive samplingmethod, questionnaire as an instrument and processed using SEM approach Warp PLS6.0. The results show that the taxpayer's compliance behavior, the taxpayer's willingnessto negotiate, the provision of financial statements based on earnings management has apositive impact on tax obligations as measured by the amount of valuntary taxcompliance, but the tax morale of taxpayers has a negative impact on tax obligationsincurred. measured based on the value of valuntary tax compliance, taxpayer compliancebehavior, willingness of taxpayers to negotiate, provision of financial reports based onearnings management mediating the perception of MSMEs' fiscal policy having apositive impact on tax obligations as measured by the value of valuntary tax compliance,while the tax morale they have Taxpayers mediate the perception of MSMEs' fiscal policyhaving a negative impact on valuntary tax compliance. Recently, it was found thatobedient taxpayers in carrying out their tax obligations are influenced by the behavior oftaxpayers, not because of regulations, behavior is seen from economic and financialconditions using a fiscal policy approach for MSMEs and a conceptual approach that isbased on a developing view of the tax policy.